Strategic Interest Projection in South China Sea Conflict - Iswardani, Denik (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2015)
This article attempts to analyze the theoretical overview of China, United States of America, and Southeast Asia countries strategic interest in South China Sea conflict. This study is carried by projecting their national interest in South China Sea and analyzed them theoretically by using Balance of Influence Theory and Hedging Strategy. The purpose of this study was to analyze the strategy of Southeast Asian countries and extra regional powers (China and US) used to keep each other constructively and cooperatively engaged in the region and to promote rule and norm-based arrangements and principles that help them to achieve their national interest and deny intramural hegemony in South China Sea